Bayesowska estymacja parametrów mieszanek rozkładów o nieznanej liczbie składników - Biskup, Dariusz (Bayesian estimation of mixtures with unknown number of components, 2006)
The paper describes in detail the Reversible Jump Markov Chain Monte Carlo algorithm which is used in the Bayesian model choice. One of the frequently met model choiceproblems involves finding the number of components in a mixture of distributions. The paper describes the case in which the mixture component is univariate normal distribution. The algorithm is illustrated with some simulation and real-life examples. The real-life examples use the data on air pollution in the Lower Silesia region of Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 9-26